Abraham Lincoln A Press Portrait - Mitgang, Herbert (The North's Civil War, 2023)
This striking portrait of Abraham Lincoln found in this book is drawn entirely from the writing of his contemporaries and extends from his political beginnings in Springfield to his assassination. It reveals a more severely beleaguered, less godlike, and finally a richer Lincoln than has come through many of the biographies of Lincoln written at a distance after his death. To those who are familiar only with the various "retouched" versions of Lincoln's life, Abraham Lincoln: A Press Portrait will be a welcome-if sometimes surprising-addition to the literature surrounding the man who is perhaps the central figure in all of American history. The brutality, indeed that malignancy of some of the treatment Lincoln received at the hands of the press may well shock those readers who believe the second half of the twentieth century has a monopoly on the journalism of insult, outrage, and indignation. That Lincoln acted with the calm and clarity he did under the barrage of such attacks can only enhance his stature as one of the great political leaders of any nation at any time. Herbert Mitgang is author of several books, including Once upon a Time in New York, The Man Who Rode the Tiger, The Letters of Carl Sandburg, The Return, America at Random, and Working for the Reader